Curricular Integration, a path for the training process in the health area, a perspective from Veterinary Medicine (Revista Sistemas de Producción Agroecológicos, 2023)
Curriculum integration (CI) is a development model used in critical-type proposals, which focus on learning, and therefore, provide proposals with an emphasis on the student, seeking to achieve significant learning. The CI is an alternative to respond to these needs, and for this it establishes the elements to integrate and the didactic strategies to achieve it, according to the graduation profile. This article characterizes the current use of CI in professional programs in the health area, the relevant elements of said experiences, and identifies the most widely used didactic strategies in its implementation, through a bibliographical consultation in scientific databases (PubMed, ScienceDirect, ClinicalKey, ERIC and Scielo) and the analysis of the levels of research corresponding to the subject, both in training in Veterinary Medicine and in other health programs. The results show the relevance of approaches such as "One Health" and Interprofessional Education (IPE), so that a curriculum with IC contributes to responding to health problems derived from Human - Animal - Environment interaction.
Keywords: Curricular integration; learning; Research